An outline of phenomenological analysis of longing - Płoszczyniec, Antoni (Hybris, 2014)
In this article I attempt to consider the structure of specific acts of desire, which are defined as ‘longing’. For that purpose, I used descriptive-analytical method of phenomenology to present the most essential aspects of this feeling. Longing, as an emotion, is a kind of insight into the sphere of values, through which the object of longing appears as a kind of good, which nature isn’t described in utilitarian or hedonistic categories. Object of longing seems to be something above those two kinds of values. Much attention was devoted to the issue of constitution of object of longing as something negative, absent for person, who misses someone or something. At the end of the paper, I make some remarks about ‘privacy’ and intimacy of longing and I consider longing as a kind of mood, through which some acts of awareness are becoming possible.